(untitled) (Student Conference Proceedings, 2025)
This study examined the biomechanical performance of intramedullary nail implants for distal fibula fractures, particularly Weber B fractures. Simplified three-dimensional models were created to simulate the biomechanics of the leg during standing. Simulations were conducted with an axial load of 70 Newtons, with the fibula bearing 20 % of the total load from the body weight shared evenly between both legs. The results demonstrated that the intramedullary nail exhibited significantly lower stress levels compared to the traditional plate and screw construct. Peak Von Mises stress levels were 26 MPa in the nail’s syndesmotic screw and 146 MPa at the screw-to-plate interface within the plate construct. These findings provide a rationale for the hypothesis that patients may be able to bear weight earlier after surgery.